BrainMeta'   Connectomics'  

Welcome Guest ( Log In | Register )

Viewing Profile: PJS
PJS

Awakening
***

Member Group: Basic Member
Joined: Aug 17, 2006

Active Stats
User's local time Oct 21, 2017, 04:17 AM
Total Cumulative Posts 216
( 0.1 posts per day / 0.16% of total forum posts )
Most active in What is God?
( 95 posts / 45% of this member's active posts )
Last Active 7th January 2012 - 05:35 PM
Status User is offline (Offline)
Communicate
AIM No Information
Yahoo No Information
ICQ No Information
MSN No Information
Contact Send a Personal Message
Contact Send an Email
Information
Home Page No Information
Birthday No Information
Location No Information
Interests No Information
Additional Information
No Information

Signature
x^2 + 1 = 0

x^3 - 2x^2 = 1
-2x^2 = (i^2/x^2) - x^3
-2 = (i^2/x^2/x^2) - (x^3/x^2)
1 = (i^2/-2) - (x/-2)
1 = 0.5 - -0.5
x/-2 = -0.5
x = 1 this is a contradiction from x^3 = -1,
x^3/x^2 = -1/-1 = x = 1, if x = 1 then x^3 equals 1 as well.
However the equation shows that x^3 = -1. x therefore becomes -1 and 1
at the same time proving that x^2 = -1 is a mathematical error.
Lo-Fi Version Time is now: 21st October 2017 - 04:17 AM


Home     |     About     |    Research     |    Forum     |    Feedback  


Copyright BrainMeta. All rights reserved.
Terms of Use  |  Last Modified Tue Jan 17 2006 12:39 am

Consciousness Expansion · Brain Mapping · Neural Circuits · Connectomics  ·  Neuroscience Forum  ·  Brain Maps Blog
 · Connectomics · Connectomics  ·  shawn mikula  ·  shawn mikula  ·  articles